PENGARUH MODEL PEMBELAJARAN EXAMPLE NON EXAMPLE TERHADAP HASIL BELAJAR SISWA KELAS V PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI UPTD SD NEGERI 122384 - Simanjuntak, Melvin; Esti Marlina Sirait; Cintami Elisabet Situmorang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to identify the effect of the Example Non Example learning model on students’ learning outcomes in Grade V at UPTD SD Negeri 122384 Pematangsiantar in the 2025/2026 academic year. The research approach used is quantitative with a Pre-Experimental design, specifically the One Group Pretest-Posttest Design. The research sample consisted of all 20 Grade V students of UPTD SD Negeri 122384 Pematangsiantar. Data were collected through a multiple-choice test consisting of 20 items, which had previously undergone validation, reliability testing, item discrimination analysis, and difficulty level assessment. The data were analyzed using the score improvement test (N-Gain).The results showed that the students’ average pretest score was 45.5 with a mastery level of 10%, which then increased to 87 with a mastery level of 90% in the posttest. The average N-Gain score of 0.7831 indicated a high improvement category, with a learning effectiveness of 78.31%. These findings indicate that the Example Non Example learning model had a significant effect on the learning outcomes of Grade V students in Pancasila Education.